A Comparative Study between Dusting and Fragmentation in Intracorporeal Laser Lithotripsy in Distal Ureteric Stone - H. Alawi Al Sunboli, Mostafa; B. Ismail, Mohammed; J. Hameed, Raghib (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Ureteric stones, commonly have an impact on the quality of life of the patient. There are many treatment choices for the condition including medical treatment, extra-corporeal shock wave lithotripsy (ESWL), endoscopic intervention by ureteroscope (URS), or surgery (open or laparoscopic). Semi-rigid URS with laser lithotripsy is used to fragment ureteric stones especially those in the distal ureter.Objectives: To assess the efficacy and complications of the dusting versus the fragmentation method for lower ureteric stones using holmium laser lithotripsy by analyzing intra-operative and post-operative variables.Patients and Methods: One hundred and twenty patients with distal ureteric stones were included in the current study which was conducted in Ghazi AL-Hariri Teaching Hospital for Surgical Specialties during the period from December 2020 to July 2022. The cases were divided into two groups: The dusting group and the fragmentation group. Both groups are further subdivided into the 10-15 mm stone group and the < 10 mm stone groups. The time of the operation, the rate of being stone-free, stone size, the rate of double-J stents (DJS), and intraoperative complications were compared for the study groups. Results: the operative time was more among Group A (dusting) than in Group B (fragmentation) with statically significant association, with a stone-free rate more in Group A (dusting) than in Group B (fragmentation) without a statically significant Need for DJ more in group b (fragmentation) than group a (dusting) with statically significant association Regard intraoperative complication (mucosal injury, stone migration, perforation) more in group b (fragmentation)than group a (dusting) without any significant association  Conclusion: The dusting method resulted in fewer intraoperative complications (mucosal injury, stone migration, perforation) and a lower need for DJ insertion than the fragmentation method. However, it needed a longer operative time than the fragmentation method.